A Systematic Review of Anogenital Distance and Gynecological Disorders: Endometriosis and Polycystic Ovary Syndrome - Pan, Zhenyan; Zhu, Fangfang; Zhou, Kai (Frontiers in Endocrinology, 2021)
Background and aim: Anogenital distance (AGD) can serve as a life-long indicator of androgen action in gestational weeks 8–14. AGD has been used as an important tool to investigate the exposure to endocrine-disrupting compounds in newborns and in individuals with male reproductive disorder. Endometriosis and polycystic ovary syndrome (PCOS) are two common gynecological disorders and both are related to prenatal androgen levels. Therefore, we performed a systematic review to evaluate the relationships of AGD with these gynecological disorders. Methods: PubMed, Web of Science, and Embase were searched for published studies up to January 25, 2021. No language restriction was implemented. Results: Ten studies were included in this review. Five focused on women with endometriosis, and six investigated women with PCOS. According to these studies, PCOS patients had longer AGD than controls, while endometriosis patients had shorter AGD than controls. In conclusion, this study provides a detailed and accurate review of the associations of AGD with endometriosis and PCOS. Conclusion: The current findings indicate the longer AGD was related to PCOS and shorter AGD was related to endometriosis. However, further well-designed studies are needed to corroborate the current findings.